PROTOTYPE DESIGN OF PLATE ROLLER MACHINE - Danang Murdiyanto; Bernardus Crisanto Putra Mbulu; Bernadus Daniel Wahyu Prasetya (Universitas Katolik Widya Karya Malang, 2023)
Current development of manufacturing industry is expected to have a good and innovative system. Machine planning is a very important part in determining the manufacturing process. Machine prototypes are very important in model and product development, because they can help a designer to evaluate processes, machine performance, and product developments. In this study, a prototype design of a plate roll machine was made. One of the manufacturing processes that is widely used in companies and home industries is the rolling process. Plate roll machine prototype design to find suitable dimensions. The plate roll machine prototype will be made using a 3D printing machine with Polylatic Acid (PLA) material. The prototype plate rolling machine uses a synchronous electric motor type 60KTYZ which has a power of 14 watts and a rotation of 15 rpm. The prototype of this plate rolling machine was tested using aluminum plate as raw material with a length of 820 mm, a width of 10 mm and a thickness of 2 mm. The test results with a given compressive force of 75 N, namely a deflection of 9 mm with a rolling speed of 0.02 m/s. In the equilibrium test, it is produced by calculating structural statics that the action forces and reaction forces are proven to be balanced.